Zinc Affects Differently Growth, Photosynthesis, Antioxidant Enzyme Activities and Phytochelatin Synthase Expression of Four Marine Diatoms. (3rd May 2012) - Nguyen-Deroche, Thi Le Nhung; Caruso, Aurore; Le, Thi Trung; Bui, Trang Viet; Schoefs, Benoît; Tremblin, Gérard; Morant-Manceau, Annick
Abstract : Zinc-supplementation (20  μ M) effects on growth, photosynthesis, antioxidant enzyme activities (superoxide dismutase, ascorbate peroxidase, catalase), and the expression of phytochelatin synthase gene were investigated in four marine diatoms ( Amphora acutiuscula, Nitzschia palea, Amphora coffeaeformis and Entomoneis paludosa ). Zn-supplementation reduced the maximum cell density. A linear relationship was found between the evolution of gross photosynthesis and total chlorophyll content. The Zn treatment decreased the electron transport rate except in A. coffeaeformis and in E. paludosa at high irradiance. A linear relationship was found between the efficiency of light to evolve oxygen and the size of the light-harvesting antenna. The external carbonic anhydrase activity was stimulated in Zn-supplemented E. paludosa but was not correlated with an increase of photosynthesis. The total activity of the antioxidant enzymes did not display any clear increase except in ascorbate peroxidase activity in N. palea . The phytochelatin synthase gene was identified in the four diatoms, but its expression was only revealed in N. palea, without a clear difference between control and Zn-supplemented cells. Among the four species, A. paludosa was the most sensitive and A. coffeaeformis, the most tolerant. A. acutiuscula seemed to be under metal starvation, whereas, to survive, only N. palea developed several stress responses.